Highly Efficient and Broadband Upconversion of NIR Sunlight with Neodymium‐Doped Glass Ceramics. Issue 4 (4th March 2015) - Skrzypczak, Ulrich; Seifert, Gerhard; Schweizer, Stefan
<x xml:space="preserve">Abstract</x> Efficient and broadband upconversion of NIR light below the silicon bandgap is a major challenge in silicon photovoltaics. All current approaches use erbium‐based systems being well optimized for monochromatic upconversion. However, to achieve an appreciable increase of photovoltaic efficiency via photon upconversion, broadband operation of the upconversion process is required. Using our comprehensive, experimentally verified rate equation system, we show numerically that neodymium can be a highly efficient broadband upconverter of NIR photons for concentrated sunlight. When embedded into a low phonon ZBLAN‐based glass ceramic, broadband upconversion efficiencies of about 10% can be reached. Moreover, its emission spectrum shifts towards the green spectral range being the optimal range for silicon absorption.